2008
DOI: 10.1093/humrep/den330
|View full text |Cite
|
Sign up to set email alerts
|

Prospective controlled trial of an electrophoretic method of sperm preparation for assisted reproduction: comparison with density gradient centrifugation

Abstract: This pilot study demonstrates that membrane-based electrophoresis is as effective as DGC in preparing sperm for IVF and ICSI, although it takes only a fraction of the time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(32 citation statements)
references
References 28 publications
0
32
0
Order By: Relevance
“…Moreover, the effectiveness of this approach has been demonstrated in case studies where conventional methods have been ineffective in isolating spermatozoa that are capable of fertilization and the initiation of normal embryonic development (Ainsworth et al, 2005(Ainsworth et al, , 2007. Recently, more extensive clinical trials have supported the practical, clinical utility of this system in the preparation of spermatozoa for ART (Fleming et al, 2008).…”
Section: Selective Isolationmentioning
confidence: 99%
“…Moreover, the effectiveness of this approach has been demonstrated in case studies where conventional methods have been ineffective in isolating spermatozoa that are capable of fertilization and the initiation of normal embryonic development (Ainsworth et al, 2005(Ainsworth et al, , 2007. Recently, more extensive clinical trials have supported the practical, clinical utility of this system in the preparation of spermatozoa for ART (Fleming et al, 2008).…”
Section: Selective Isolationmentioning
confidence: 99%
“…128 Comparison of density-gradient centrifugation of spermatozoa using the ISolateTM medium with the electrophoretic method revealed comparable results of sperm recovery, motility and DNA damage. 129 Recent investigations by Aitken et al 130 and Ainsworth et al 131 demonstrated that electrophoretically separated human spermatozoa are free of oxidative stress, capacitate and bind to zona pellucida normally. The technique does not result in a skewing of the ratio of X-and Y-bearing germ cells as suspected by others.…”
Section: Electrical Chargementioning
confidence: 99%
“…The study involved a couple with long-term infertility associated with extensive sperm DNA damage. Later, a prospective controlled trial was performed to demonstrate that the membrane-based electrophoresis system is as effective as and considerably faster than the DGC to prepare spermatozoa for both IVF and ICSI (Fleming et al, 2008). …”
Section: Electrophoretic Systemmentioning
confidence: 99%